Dynamics of Rice Prices in Indonesia: The Impact of Agricultural Regulations on Rice Quality - Trisulo, Trisulo; Gomes, Lucio Marcal; Wisetsri, Warakamol (Buletin Ilmiah Impas, 2025)
Rice price volatility in Indonesia remains a critical issue, affecting both consumer affordability and farmer profitability. Despite government interventions, significant price fluctuations continue, driven by regulatory changes, macroeconomic factors, supply chain inefficiencies, and climate-related disruptions. The implementation of Permentan No. 31/2017 modified rice classification standards, potentially altering market price structures and consumer purchasing behavior. This study aims to analyze the dynamics of rice prices in Indonesia in 2023, focusing on the impact of government regulations, seasonal supply variations, and external economic pressures. It examines how Permentan No. 31/2017 influenced rice price differentiation, as well as the effectiveness of BULOG’s price stabilization efforts in mitigating price volatility. This research adopts a quantitative approach, utilizing secondary data from BPS Indonesia. Monthly price trends for Premium, Medium, and Low/Non-Quality rice were analyzed from January to December 2023. A comparative assessment was conducted to examine price disparities before and after regulatory adjustments, as well as the correlation between seasonal supply cycles and price fluctuations. Findings indicate that rice prices remained stable in the first half of 2023 but surged significantly between August and December. Premium rice peaked at IDR 13,371.54 per kg, Medium-quality rice reached IDR 13,011.56 per kg, and Low/Non-Quality rice increased to IDR 12,381.31 per kg in October. The narrowing price gap between Premium and Medium rice in early 2023 suggests that regulatory changes influenced classification and market pricing. The study highlights the complex interplay between agricultural regulations, macroeconomic factors, and environmental risks in shaping rice price volatility. While Permentan No. 31/2017 affected price differentiation, broader market pressures drove significant instability. Future research should focus on strengthening domestic rice production efficiency, improving supply chain resilience, and enhancing government intervention strategies. Further exploration of the link between rice price inflation and household food security, as well as adaptive strategies for climate-resilient rice farming, will be crucial for ensuring long-term stability in Indonesia’s rice market. Keywords: Rice price volatility, agricultural regulations, supply chain inefficiencies, , food security, rice classification